Free Ships, Free Goods: The US Diplomacy in Searching for Freedom of Navigation in International Trade - Sang, Nguyen Van; Nam, Le Thanh; Binh, Nguyen Tuan; Quy, Nguyen Duy (Journal of Ecohumanism, 2024)
The article aims to analyse the US struggle to establish freedom of navigation in international trade during the XVIII-XIX century. For this purpose, the study focuses on clarifying the following aspects: the view of freedom of navigation of the US in the early days of the founding father area; obstacles for the nascent nation in international trade; American diplomacy with the struggle to break the rules and practices of navigation from the Great Britain. The success of the struggle, the article concluded, contributed to strengthening the Federation internally, establishing its place in international maritime trade.